1996
DOI: 10.1139/v96-069
|View full text |Cite
|
Sign up to set email alerts
|

Standard state heat capacities of aqueous electrolytes and some related undissociated species

Abstract: Uses of heat capacities of solutions of electrolytes are reviewed, with a particular emphasis on the standard state partial molar heat capacities and their applications to calculations of the effects of temperature on equilibrium constants, electrode potentials, enthalpies, and entropies. Methods of obtaining these standard partial molar heat capacities are summarized, followed by comparisons of values obtained in different ways. Many of the "best" such heat capacities are collected and then used as the basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 74 publications
7
24
0
Order By: Relevance
“…Calculated lines: blue  , this study; black  , ref ; red , ref . Symbols: ○, ref △, ref □, refs and .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Calculated lines: blue  , this study; black  , ref ; red , ref . Symbols: ○, ref △, ref □, refs and .…”
Section: Resultsmentioning
confidence: 92%
“…The most correct approach to determine the contributions of individual species is the joint processing of data on heat capacities of various compounds containing them. It has been carried out for Ca 2+ and NO 3 – ions by a number of authors; however, their results are usually limited to 298.15 K. An exception is the HKF EoS, which is used to describe and predict the standard state thermodynamic properties of aqueous species over a wide temperature range. It was shown that the values of C̅ p ,2 ° at high temperatures, predicted by the HKF EoS based on the data at moderate temperatures, are in good agreement with experiment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…9,10 The agreement is close to the likely limits of uncertainty of (1 to 2) J‚K -1 ‚mol -1 in C pφ . 11 Thus correction for heat losses in the calorimeter was considered unnecessary.…”
Section: Resultsmentioning
confidence: 99%
“…The last term on the righthand side is the so-called relaxation term [27], accounting for the thermal shift associated with the change in equilibrium composition during the measurement of the solution heat capacity. The degree of association was calculated again from the thermodynamic association constant and activity coefficient models reported by Simonson et al [24] and term ð@a=@TÞ p was evaluated numerically.…”
Section: Tablementioning
confidence: 99%